Pengaruh E-Service Quality terhadap E-Loyalty pada Pengguna Aplikasi Blibli.com - Razati, M.Si, Girang - (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
This study aims to determine the dimensions of customer engagement and customer loyalty dimensions. The design of this study was cross sectional using an explanatory approach through an explanatory survey method. Blibli.com customer analysis unit of 200 respondents. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is an explanatory technique using frequency distribution and path analysis. Based on the results of the study using path analysis, the results show that e-service quality has a positive effect on e-loyalty with a strong category. The most dominant dimension of e-service quality influences e-loyalty, namely efficiency and the least dominant influence of e-service quality dimensions, the dimensions of privacy.